Hitaveita Reykjavikur after 60 Years of Operation - Development and Benefits - Frimannsson, Hreinn (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 1991)
Reykjavik District Heating Services (Hitaveita Reykjavikur) was established in 1930. It started small but it has grown continuously and now serves 140,000 inhabitants of Iceland, i.e., 57% of the nation. The Hitaveita uses four different low temperature fields and one high temperature field. The water from the low temperature field is used directly in the radiators and as tap water; but, the energy from the high temperature field is used to heat up fresh water. The energy from the Hitaveita is mainly used for space heating. The cost of the energy is 1.5 cents/kWh and the exploitation of geothermal energy has low environmental impact, especially the low temperature fields. The nearest alternative energy options are electricity and fossil fuels. The cost of heat from those sources is over 5 cents/kWh and the negative impact from those is supposed to be larger than from the geothermal. The conclusion is, therefore, that geothermal energy has economical and environmental advantages the alternative energy sources can not compete with